PENGEMBANGAN MODEL KEMATANGAN TRANSFORMASI LAYANAN DIGITAL PADA SEKTOR PUBLIK - Fahmi Zakiuddin, Naufal
Digital service transformation is a transformation carried out on digital service products. Digital services transformation in the public sector is carried out with the aim of increasing public values such as community satisfaction, saving government budgets, and bureaucratic efficiency. In the digital service transformation process, a maturity model is needed to measure how far the realization of the digital service transformation process is compared to the expected transformation target. Until now there have been several studies that have discussed digital service transformation maturity models for the public sector. However, the existing models still address specific domains. There is no generic maturity model for the public sector yet. The maturity model for transforming digital services in the public sector is important to study because the government as the public sector needs to know the extent to which the transformation they are carrying out has been achieved according to the planned targets. The maturity model built is expected to be able to describe each component that influences the digital service transformation process and can show the maturity level of digital services for each of these components. This model will be built using the Design Science Research Methodology. This research has several stages of implementation starting from problem identification, setting goals, developing models, demonstrations, evaluations, to publication. Evaluation of the built model is a case study because the artifacts in this study are naturalistic and ex post. With case studies, it is hoped that the models that have been developed are proven to be able to solve problems in the real world. The digital service transformation maturity model was successfully developed and tested. The maturity model design process concluded with in-depth expert interviews. The developed maturity model was applied in a case study on the Service Management Division of the Central Bureau of Statistics of the Republic of Indonesia (BPS RI). The case study results indicated the maturity level of the Service Management Division of BPS RI. The case study also highlighted the overall implementation of the digital service transformation process, including its strengths and weaknesses. It is hoped that